A Type of Rural Houses or a Cultural Heritage That Tending to Disappear: Beehive Houses of Suruç - Şahinalp, Mehmet Sait (Gaziantep University, 2018)
Beehive houses of Suruç are completely built from sun dried mudbrick. Traditionally, rural house of Suruç plain is beehive houses. It has known that these houses have been used for centuries. These houses rooms have square plan and each room have conical roof. In terms of their own characteristic, Suruç beehive houses different from other conical or dome roofed houses such as beehive house of Harran, Trullo and Clochán. Basically there are four usage spaces; living rooms, designs of granaries, barn or folds and haylofts which are respectively arranged from south to north. These usage spaces are connected to each other with eyvans or gates without door. As requirement of rural life, these houses have some outbuildings such as tendur (tandoor), kadin (hayloft), gom (open folder), ça’l, lod and seki (terrace). Due to some environmental and socio-economic problems have caused migration from countryside to cities during the last 30 years. As a result of this, the Suruç beehive houses have either disused or abandoned completely. In addition, especially in last 30 years, the villagers in the area have begun to prefer building the reinforced concrete houses. This has led some of the Suruç beehive houses either to be destroyed or abandoned. Recent survived examples of these houses can be seen in Kara, Yatırtepe and Boztepe villages